THE EFFECT OF CAPITAL STRUCTURE ON SHARE PRICE ON PROPERTY AND REAL ESTATE COMPANIES LISTED ON INDONESIA SHARE EXCHANGE - Puja Rizqy Ramadhan; Oktarini Khamilah Siregar; Suci Pratiwi (CERED Indonesia Institute, 2020)
Share prices are prices that occur in the share market at a certain time determined by market participants and determined by the demand and supply concerned in the capital market. Share price is one indicator of a company's success because high share prices will provide benefits, namely capital gains and the company's growth prospects can also be seen from the movement of share prices so that investors in general will be more interested in investing their capital in companies that provide them with profits. Several factors affect share prices, namely capital structure and company size.The purpose of this study was to determine whether capital structure affects share prices on Property and Real Estate Companies listed on the Indonesia Share Exchange. The sample in this study was using puposive sampling with a total sample of 10 Property and Real Estate Companies listed on the Indonesia Share Exchange and data from 2014 - 2017. The results of this study indicate that the capital structure partially has a negative and insignificant effect on share prices on Property and Real Estate Companies listed on the Indonesia Share Exchange